Pengaruh Jenis Varietas dan Macam Auksin Sintetis Terhadap Pertumbuhan Stek Anggur (Vitis vinifera L.) - Oktaviana, Safitri Qory; Zuhroh, Mimik Umi; Hartanti, Aprilia (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
Grapes are one of the fruits from sub-tropical regions that have adapted to the climate of the Indonesian region. Increasing grape production needs to be done through various plant propagation techniques considering that grape productivity in Indonesia is still relatively low. One of the plant propagation techniques that can be applied to grapes is cuttings.The aims of the research were: 1) To determine the type of variety that affected the growth of grape cuttings (Vitis vinifera L.), 2) To determine the type of synthetic auxin that affected the growth of grape cuttings (Vitis vinifera L.), 3) To determine whether there was an interaction between varieties and types of auxin on the growth of grape cuttings grape cuttings (Vitis vinifera L.).The study was conducted using a factorial randomized block design (RAK) with 2 factors. The first factor was the type of variety (Kediri Kuning, Prabu Bestari, and Bali varieties) and the second factor was the type of synthetic auxin (IBA, NAA, IAA) which was repeated 3 times.The results showed that: 1) Single-variety treatment had a significant effect on the treatment of the Prabu Bestari (J2) variety on the growth of grape cuttings (Vitis vinifera L.). 2) The single treatment of synthetic auxin had a significant effect on the treatment of auxin IBA (Z1) on the growth of grape cuttings (Vitis vinifera L.). 3) There was an interaction between varieties and synthetic auxins in the combination treatment of Prabu Bestari and NAA (J2Z2) varieties on the growth of grape cuttings (Vitis vinifera L.).Keywords: Types of Varieties, Kinds of Synthetic Auxins, Grape Cuttings.